1994
DOI: 10.1007/bf02215713
|View full text |Cite
|
Sign up to set email alerts
|

Developmental blockage of mouse embryos caused by fatty acids

Abstract: These results suggest that lipid radicals can easily be generated in early stage embryos and that blastomeres are among the cells vulnerable to the damage by lipid peroxidation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0
1

Year Published

1996
1996
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(40 citation statements)
references
References 26 publications
1
38
0
1
Order By: Relevance
“…In the present study, maturation of oocytes in the presence of LA at 50 mM (which has no significant inhibitory effect on oocyte maturation and cumulus expansion) and 100 mM significantly decreased the cleavage and blastocyst rate. In a previous study, similar effects were reported when mouse pronuclear and two-cell stages were treated by LA in vitro (Nonogaki et al 1994). These authors also showed that the addition of antioxidants to embryo culture media could attenuate the rate of developmental blockage, suggesting that the effect was caused by damage of the cells by lipid peroxidation.…”
Section: Discussionsupporting
confidence: 69%
“…In the present study, maturation of oocytes in the presence of LA at 50 mM (which has no significant inhibitory effect on oocyte maturation and cumulus expansion) and 100 mM significantly decreased the cleavage and blastocyst rate. In a previous study, similar effects were reported when mouse pronuclear and two-cell stages were treated by LA in vitro (Nonogaki et al 1994). These authors also showed that the addition of antioxidants to embryo culture media could attenuate the rate of developmental blockage, suggesting that the effect was caused by damage of the cells by lipid peroxidation.…”
Section: Discussionsupporting
confidence: 69%
“…Fatty acyl residues have previously been shown to be associated with oocyte maturation and fertility ( 18 ) as well as with embryo development ( 19,35,41,42 ) in mammalian species. As an example, storage and membrane lipid con- known to present the high sensitivity needed to detect the few picomols of lipids present in these samples.…”
Section: Discussionmentioning
confidence: 99%
“…Nonogaki et al (1994) observed an arrest in embryo development after exposure of mouse zygotes to high concentrations of PUFAs (linoleic and α-linolenic acid). Also, oocyte exposure to a maternal environment enriched with n-3 PUFA (diet supplemented with n-3) resulted in altered mitochondrial distribution and calcium levels and increased ROS production (Wakefield et al, 2008).…”
Section: Fa Composition Of Ff In Relation To the Diet And Its Influenmentioning
confidence: 98%